An RNA-binding regulatory cascade controls the switch from proliferation to differentiation in the Drosophila male germ cell lineage - Devon E. Harris; Jongmin J. Kim; Sarah R. Stern; Hannah M. Vicars; Neuza R. Matias; Lorenzo Gallicchio; Catherine C. Baker; Margaret T. Fuller (Proceedings of the National Academy of Sciences, 2025)
The switch from precursor cell proliferation to onset of differentiation in adult stem cell lineages must be carefully regulated to produce sufficient progeny to maintain and repair tissues, yet prevent overproliferation that may enable oncogenesis. In the Drosophila male germ cell lineage, spermatogonia produced by germ line stem cells undergo a limited number of transit amplifying mitotic divisions before switching to the spermatocyte program that sets up meiosis and eventual spermatid differentiation. The number of transit amplifying divisions is set by accumulation of the bag-of-marbles (Bam) protein to a critical threshold. In bam mutants, spermatogonia proliferate through several extra rounds of mitosis and then die without becoming spermatocytes. Here, we show that a key role of Bam for the mitosis to differentiation switch is repressing expression of Held Out Wings ( how ), homolog of mammalian Quaking. Knockdown of how in germ cells was sufficient to allow spermatogonia mutant for bam or its partner benign gonial cell neoplasm to differentiate, while forced expression of nuclear-targeted How protein in spermatogonia wild-type for bam resulted in continued proliferation at the expense of differentiation. Our findings suggest that Bam targets how RNA for degradation by acting as an adapter to recruit the CCR4-NOT deadenylation complex via binding its subunit, Caf40. As How is itself an RNA-binding protein with roles in RNA processing, our findings reveal that the switch from proliferation to meiosis and differentiation in the Drosophila male germ line adult stem cell lineage is regulated by a cascade of RNA-binding proteins.